Cooperative Learning in EFL Classrooms: The Role of Effective Group Processing in Enhancing Teaching and Learning Outcomes - Wijaya, Nada Niti Joko; Wiyaka, Wiyaka; Sukmaningrum, Rahmawati (Universitas PGRI Semarang, 2022)
This paper examines the role of cooperative learning in enhancing language proficiency and social development in EFL classrooms. Effective language acquisition requires students to develop the four language skills, master linguistic elements, and understand cultural contexts essential for communication. However, limited opportunities to practice English outside the classroom hinder students’ progress. Cooperative learning addresses this challenge by promoting meaningful interaction and collaboration. According to Smith (1996), cooperative learning involves small groups where students work together to maximize their learning outcomes. Effective group processing within cooperative learning not only fosters the sharing and refining of strategies but also encourages learners to view language acquisition as a collaborative endeavor. Despite its benefits, many teachers fail to distinguish between merely placing students in groups and fostering genuine cooperation. Kessler (1992) emphasizes that successful cooperative learning requires structured activities that promote accountability, interdependence, and commitment to group goals. This study highlights the importance of carefully managing group dynamics and offers strategies for building effective cooperative groups in EFL contexts. Findings suggest that structured cooperative learning enhances students' language proficiency, engagement, and interpersonal skills, ultimately contributing to more successful learning outcomes.